2022
DOI: 10.1007/s10311-022-01465-2
|View full text |Cite
|
Sign up to set email alerts
|

Methods to alleviate the inhibition of sludge anaerobic digestion by emerging contaminants: a review

Abstract: The rising occurrence of emerging contaminants in sludges both inhibits the anaerobic digestion of sludges and induces health issues when sludges are recycled in agriculture, calling for methods to remove contaminants. Here we review emerging pollutants in wastewater treatment plants, before and after anaerobic digestion. We present their inhibitory effects and remediation methods to alleviate inhibition. Pharmaceuticals have been detected in about 50% of the sludge samples. Sewage sludge contaminants include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 235 publications
(211 reference statements)
0
6
0
Order By: Relevance
“…The concentrations of pharmaceuticals in municipal sewage sludge are lower; they barely reach 100 µg/L. The total content of pharmaceuticals in sewage sludge included diuretics (19%), lipid-modifying agents (16-21%), diclofenac, hydrochlorothiazide, clarithromycin, furosemide, atorvastatin, and carbamazepine [51]. The mean concentrations of selected pharmaceuticals in sewage sludge applied to agricultural land were 125 µg/kg d.w. [53].…”
Section: The Presence Of Pharmaceuticals In the Environment And Its D...mentioning
confidence: 99%
“…The concentrations of pharmaceuticals in municipal sewage sludge are lower; they barely reach 100 µg/L. The total content of pharmaceuticals in sewage sludge included diuretics (19%), lipid-modifying agents (16-21%), diclofenac, hydrochlorothiazide, clarithromycin, furosemide, atorvastatin, and carbamazepine [51]. The mean concentrations of selected pharmaceuticals in sewage sludge applied to agricultural land were 125 µg/kg d.w. [53].…”
Section: The Presence Of Pharmaceuticals In the Environment And Its D...mentioning
confidence: 99%
“…Based on the waste sources, research has demonstrated that industrial waste is the primary source of waste (Gaur et al 2020 ). This waste is mainly composed of volatile compounds, wastewater, slag, and scrap generated during industrial production, which contain many hazardous substances, such as heavy metals, organic pollutants, and radioactive materials, leading to severe environmental pollution (Patel et al 2022 ; Tawfik et al 2022 ). Additionally, organic waste is generated by agricultural, animal, and wastewater treatment waste and the food industry.…”
Section: Waste Types and Productionmentioning
confidence: 99%
“…However, the appearance of emerging contaminants in sludge can eventually inhibit anaerobic digestion and can induce health problems when sludge is recycled to agriculture, requiring methods to remove contaminants either before or after anaerobic treatment. Some of the pollutant remediation methods include electrooxidation, ultrasonication, thermal hydrolysis, ozonation, and bioaugmentation [ 191 ]. Concurrently, a diluted DS would be obtained, which, depending on its composition and intended application, can be regenerated, subjected to desalination processes to yield clean or potable water, or even utilized directly as fertilizer for irrigation purposes.…”
Section: Wastewater Contaminationmentioning
confidence: 99%